The Earliest χρηστιανοί of Messene and Their Third- and Fourth-century Funerary Monuments - Tsivikis, Nikos (Tekmeria, 2025)
This article presents and analyzes a newly studied inscription from ancient Messene, found on an architectural block originating from a Roman funerary monument (Monument M) located extra muros near the stadium-gymnasium complex. The brief text, reading Διομή|δης | χρηστιανός, identifies a previously unknown early Christian resident of the city. Analysis of the inscription's paleography, simple nominative formula, and archaeological context suggests a date in the late third or early fourth century CE. Particular attention is paid to the orthography χρηστιανός, employing eta instead of iota. This spelling, rare in Greece but paralleled in early inscriptions from Phrygia, Thessaloniki, and documented in papyri, is interpreted as an indicator of an early, pre-standardized phase of Christian epigraphic practice, possibly reflecting the term's external Roman administrative origins before its full assimilation by the community. The inscription is contextualized within Messenian funerary traditions, arguing that Diomedes, likely an elite layman, was interred in a pre-existing family monument (originally created probably in the first or second century CE), demonstrating continuity in burial customs alongside a novel public assertion of Christian identity. This act is framed as a conscious instance of self-representation, reflecting the nascent tradition of foregrounding Christian faith as a primary identifier, akin to declarations found in martyr accounts. Diomedes constitutes the third known member of Messene's pre-Constantinian Christian community, alongside the lector Paramonos and bishop Theodoulos, offering valuable insight into the social composition and self-perception of Christianity in the city before the mid-fourth century. This finding significantly enhances our understanding of the chronology and character of early Christianity in the Peloponnese.